Hubungan Persepsi Petugas Kesehatan dengan Kepatuhan Terhadap Upaya Pencegahan Penyebaran Wabah Covid-19 di Area GBPT RSUD Dr. Soetomo - Nining Dwi Suti Ismawati; Stefanus Supriyanto; Setya Haksama (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: COVID-19 is an infectious disease caused by a newly discovered type of coronavirus. This is a new virus and a previously unknown disease before the outbreak in Wuhan, China in December 2019. A coronavirus is a group of viruses that can cause disease in animals or humans. The speed of the epidemic depends on two things, namely how many people are infected in a single case and how long it takes between people to spread the infection. Until now, 209 countries have been affected by COVID-19. The Indonesian government has made efforts to cut the spread of the COVID-19 virus with several steps, namely urging the public not to come or hold events that can gather many people. Aim of study: Based on this background, this study aims to determine whether or not there is a relationship between perceptions of health workers and adherence to the appeal for wearing masks, social distancing, and washing hands in the GBPT area of dr. Soetomo to prevent the spread of the COVID-19 outbreak. Method: The number of respondents in this study were 50 people who work as doctors, nurses, administrative staff, and transporters and were calculated using a purposive sampling technique. Data were collected using instruments in the form of questionnaires and observation checklist sheets, using the Chi-Square statistical test using the SPSS program. Results and Discussion: The results of this study indicate that there is a significant relationship between perceptions of health workers and adherence. Conclusion: It can be concluded that there is a need to wear masks in the GBPT area of Dr. Soetomo to prevent the spread of the COVID-19 outbreak to health workers, especially those who work as nurses.